FLUTTER ANALYSIS FIGHTER AIRCRAFT WING WITH CONVENTIONAL STRUCTURE CONFIGURATION - Hayati Putri, Mardiah
A fighter aircraft is an aircraft designed for defense and combat in the air. This aircraft can operate in extreme conditions because it is required to perform good maneuvers according to its mission. This of course will affect the resistance of the structure due to loading. It is necessary to analyze the possible conditions that can cause failure in the working area of the aircraft, one of which is dynamic instability. One of the dynamic instability phenomena is flutter. Flutter occurs due to the interaction between elastic forces, inertial forces, and aerodynamic forces. In order to prevent the occurrence of flutter, it is necessary to do a flutter analysis of the wing structure to determine the critical speed of flutter. This research will use IFX aircraft wing structure data. Flutter analysis was carried out on the wing model with conventional multi-spar structure obtained from previous studies. The analysis was performed numerically with MSC Nastran software. All flutter analysis results will be displayed in velocity-damping graph and velocity-frequency graph. From these two graphs, the critical flutter speed will be known. For the analysis, modifications were made to the model. Modifications are made by adding fuel and armament. All models will be analyzed on subsonic and supersonic flow with the assumption that the flight altitude is at sea level. The supersonic speed limit for the aerodynamic method used is mach 7. The results obtained show structural flutter with fuel occurs at speed of mach 7.7 which is outside the required speed. For this reason, it is necessary to decrease the stiffness and thickness of the skin to see why indication of flutter that occurs at very high speeds. Meanwhile, structural flutter with fuel and armament occurs at mach 6.64. The same steps are also taken for this structure. The results of a parametric study show that one of the causes of the very high flutter speed obtained is due to a very rigid structure. When the modulus of elasticity is reduced to 7.7% the speed decreases from 2660 m/s to 1050 m/s for the fuel structure and from 2210 m/s to 850 m/s for structure with fuel and armament. Meanwhile, lowering the thickness to 50% doesn’t produce flutter speed below 2000 m/s but did produce a local mode in the vibration mode results.